(untitled) (International Journal of Environmental Sciences, 2025)
Conserving energy and the environment depends significantly on the detection and monitoring of exhaust and toxic gases. Affordable, low-power gas sensors are highly looked after. Because of their great sensitivity and selectivity, metal oxide gas sensors are becoming more and more widely recognized. This research work discusses a fictional attempt to synthesize and characterize metal oxides, specifically titanium oxide, cerium oxide, and a combination of cerium and titanium mixed metal oxide known as CTMMO. The co-precipitation method with a microwave reaction system is employed for nanoparticle preparation, and various analytical techniques, such as FT-IR, UV-VIS(DRS), FE-SEM, EDAX, AFM, and XRD analysis, are utilized to characterize the prepared nanoparticles.The FT-IR spectrum of CTMMO indicates the formation of mixed metal oxide of cerium and titanium.The XRD pattern confirmed the cubic fluorite structure of CeO2. In this research work, the voltammetric studies were carried out at Ph 7.00 buffer solution using glassy carbon electrode to explore the use of titanium oxide, cerium oxide, and cerium titanium mixed metal oxides (CTMMO) in sensing of ammonia and hydrogen sulfideat the scan rate of 20 mV/s.The binding interaction studies of ovalbumin the protein was explored by using UV-visible absorption and fluorescence spectral methods. The impressive antibacterial properties of metal oxides and mixed metal oxides were studied against the different bacteria’susing the disc diffusion method.